PERSEPSI CIVITAS AKADEMIKA UIN MALANG TERHADAP PENGARUSUTAMAAN GENDER - Mahpur, M.Si, M. (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2006)
This research is intended to describe the perception of UIN academics on gender mainstreaming issue and to map the argument on the need of gender mainstreaming implementation which includes gender strategy and gender practice at this academic institution. Using descriptive quantitative methode, the data gathered in the form of openmind-system questionnaires distributing to the Deans, vice deans, and head of several units.The result of research reveals that either men or women at UIN Malang tend to refuse the implementation of gender mainstreaming (men=44.67% and women=25.33%). Only 35% of total amount of respondent agree to implement gender mainstreming (men=15 dan women=20%). Meanwhile, the respons toward the implementation is that word